1988
DOI: 10.1007/bf01452586
|View full text |Cite
|
Sign up to set email alerts
|

Some structural and mechanical properties of bacterially produced poly-?-hydroxybutyrate-co-?-hydroxyvalerate

Abstract: Some structural and mechanical properties of PHB homopolymer and copolymers containing 17 and 25-30 % PHV have been investigated. X-ray scattering, optical microscopy, density measurements and differential scanning calorimetry were used to interpret the results of load-elongation curves and thermomechanical softening measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 6 publications
2
35
0
Order By: Relevance
“…(PHB) and copolymers poly(3-hydroxybutyrate-When propionic acid is added to the growth medium co-3-hydroxyvalerate) (PHB/HV). [2][3][4][5][6][7][8][9][10][11] Although during conditions of nitrogen limitation, the poly-PHAs are biodegradable-microorganisms are mer produced is PHB/HV copolymer. Bacterially able to rapidly degrade PHB and PHB/HV to carproduced PHB/HV copolymers have been demonstrated to be randomly sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…(PHB) and copolymers poly(3-hydroxybutyrate-When propionic acid is added to the growth medium co-3-hydroxyvalerate) (PHB/HV). [2][3][4][5][6][7][8][9][10][11] Although during conditions of nitrogen limitation, the poly-PHAs are biodegradable-microorganisms are mer produced is PHB/HV copolymer. Bacterially able to rapidly degrade PHB and PHB/HV to carproduced PHB/HV copolymers have been demonstrated to be randomly sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…The PHA accumulated by H. mediterranei was reported to be poly(3-hydroxybutyrate) (PHB) originally (8,23) but has been reevaluated as poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) recently (5,17). PHBV has much better mechanical properties than PHB and hence is more promising for commercial production and application (1,19). Unlike PHBV production in bacteria, where costly and cellular toxic carbons, such as propionic acid or valeric acid, would be provided as the precursors of the 3-hydroxyvalerate (3HV) unit (36), H. mediterranei can accumulate PHBV up to ϳ60% (wt/wt) from starch, glucose, or other cheaper carbon sources, including industrial by-products (17,23).…”
mentioning
confidence: 99%
“…However, when the crystallized sample is cooled fast (above 80°C/min), the circle lines could not form. Some previous research works [29][30][31][32] also found the homocentric lines in different polymer spherulites; they believe that these lines are cracks, but there are no detailed characterizations of these cracks. We will study these lines in next part in detail.…”
Section: Effect Of the Film Thickness On Spherulitesmentioning
confidence: 90%
“…(2) No cracks will form in pure PTT with any film thickness. PTT is different to PLLA although similar cracks are also widely reported in poly(L-lactic acid) (PLLA) with no fibers or other polymers [29][30][31][32]. The film strength and the constriction difference of these polymers are all different to PTT.…”
Section: Surface Topography Of the Composite's Spherulitesmentioning
confidence: 92%